1995
DOI: 10.1083/jcb.130.4.847
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of calreticulin increases the Ca2+ capacity of rapidly exchanging Ca2+ stores and reveals aspects of their lumenal microenvironment and function.

Abstract: Abstract, A molecularly tagged form of calreticulin (CR), a low affinity-high capacity Ca 2+ binding protein that resides in the ER lumen, was transiently transfected into HeLa cells to specifically modify the Ca 2÷ buffering capacity of the intracellular Ca 2÷ stores. Fluorescence and confocal microscope immunocytochemistry revealed the tagged protein to be expressed by over 40% of the cells and to overlap in its distribution the endogenous CR yielding a delicate cytoplasmic network, i.e., the typical pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
148
2
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 50 publications
14
148
2
3
Order By: Relevance
“…There are several reports (9,10,56,57) (11). Consistent with these studies, the decreased cellular content of calreticulin that we observed during the physiologic process of myeloid cell differentiation correlated with a commensurate decrease in the Ca 2ϩ stores.…”
Section: Fig 8 Immunoblot Analysis Of Selected Er and Cytosolic Prosupporting
confidence: 73%
“…There are several reports (9,10,56,57) (11). Consistent with these studies, the decreased cellular content of calreticulin that we observed during the physiologic process of myeloid cell differentiation correlated with a commensurate decrease in the Ca 2ϩ stores.…”
Section: Fig 8 Immunoblot Analysis Of Selected Er and Cytosolic Prosupporting
confidence: 73%
“…The mechanisms that sustain the calcium heterogeneity within the ER remain to be identified. A role of CRT, the Ca2+-binding protein which in other cell types has been shown to play the major role in the ER lumenal storage (Treves et al, 1992;Bastianutto et al, 1995), can be excluded in PC12 based on the widespread distribution revealed by immunocytochemistry. The possibility that remains open is that of additional Ca2+-binding protein (s), not yet identified, concentrated at discrete areas of the ER lumen as it occurs with calsequestrin within the muscle sarcoplasmic reticulum (see Pozzan et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, histamine generates a typical biphasic cytosolic Ca 2ϩ signal with sustained [Ca 2ϩ ] c elevation and parallel emptying of the ER until the agonist is present (21). Activation of SOC following ER emptying has been also shown after histamine stimulation (22,23). In contrast to the H 1 receptor, the group I (Ca 2ϩ -mobilizing) metabotropic glutamate receptors, such as mGluR1 or mGluR5, undergo receptor desensitization in the continuous presence of glutamate (for a review, see Ref.…”
mentioning
confidence: 99%